An improvement of HfO2/Ge interface by in situ remote N2 plasma pretreatment for Ge MOS devices. (18th March 2016) - Chi, Xiaowei; Lan, Xiaoling; Lu, Chao; Hong, Haiyang; Li, Cheng; Chen, Songyan; Lai, Hongkai; Huang, Wei; Xu, Jianfang
Abstract: In situ remote N2 plasma pretreatment of Ge substrate before deposition of HfO2 is proved effective to reduce GeOx interlayer at the HfO2 /Ge interface, resulting in a smaller capacitance equivalent oxide thickness, lower interface trap density and leakage current density for the metal/HfO2 /n-Ge capacitors. However, it has no obvious impact on the metal/HfO2 /p-Ge capacitors, showing a much higher interface trap density than that on n-Ge. The high equivalent permittivity of the HfO2 gate stacks (∼24.2) confirmed the removal of GeOx interlayer by N2 plasma pretreatment. In situ remote N2 plasma pretreatment is demonstrated perspective to make metal/HfO2 /n-Ge MOSFET with scaling capacitance equivalent oxide thickness.